Large magnetic dipole moments for neutrinos with arbitrary non-calculable masses - Montero, J. C.; Pleitez, V (World Scientific Publ Co Pte Ltd, 2001)
We show that there is a general sort of neutrino effective interactions which allows, under certain conditions, to have relatively large magnetic dipole moments for neutrinos while keeping their masses non-calculable and arbitrarily small. The main ingredient of our mechanism for generating large magnetic moment to the neutrinos is the existence of a neutral scalar which has the only role to give mass to the neutrinos or the existence of flavor changing neutral currents in the neutrino sector. Although our approach is model independent, some models in which those interactions arise are commented.